Early Experience of TACE Combined with Atezolizumab plus Bevacizumab for Patients with Intermediate-Stage Hepatocellular Carcinoma beyond Up-to-Seven Criteria: A Multicenter, Single-Arm Study. (15th April 2023) - Wang, Kang; Zhu, Hongfei; Yu, Hongming; Cheng, Yuqiang; Xiang, Yanjun; Cheng, Zhangjun; Li, Yang; Li, Tao; Wang, Dongxu; Zhu, Zhenyu; Cheng, Shuqun
Abstract : Aim . Locoregional treatment, such as TACE, in combination with immunotherapy may elicit a synergistic anticancer effect. However, TACE combined with atezolizumab plus bevacizumab (atezo/bev) has not been investigated for patients with intermediate stage (BCLC B) HCC beyond the up-to-seven criteria. This study aims to evaluate the efficacy and safety of this treatment strategy in intermediate-stage HCC patients with large or multinodular tumors exceeding the up-to-seven criteria. Methods . This multicenter retrospective study included patients with intermediate stage (BCLC B) HCC beyond the up-to-seven criteria treated with TACE combined with atezo/bev from five centers in China from March to September 2021. The outcomes of this study included the objective response rate (ORR), overall survival (OS), and progression-free survival (PFS). Treatment-related adverse events (TRAEs) were analyzed to assess safety. Results . A total of 21 patients were enrolled in this study, with a median follow-up duration of 11.7 months. According to Response Evaluation Criteria in Solid Tumors (RECIST) version 1.1, the best ORR was 42.9% and the DCR was 100%. According to modified RECIST (mRECIST), the best ORR and DCR were 61.9% and 100%, respectively. The median PFS and OS were not reached. The most common TRAEs at all levels were fever (71.4%), and the most common grade 3/4 TRAE was hypertension (14.3%). Conclusions . TACE combined with atezo/bev showed encouraging efficacy and an acceptable safety profile, making it a promising treatment option for patients with BCLC B HCC beyond the up-to-seven criteria, which will be further investigated in a prospective single-arm trial.